Conjugated Linoleic Acid Synthesis in Milk Fermented with Lactobacillus casei Strain AG - Widodo; Sukarno, Ari Surya; Estancia, Kafaah; Widianto, Donny; Indratiningsih (Pakistan Journal of Nutrition, 2018)
Background and Objective: Conjugated linoleic acid (CLA) is a bioactive compound that can be synthesized by probiotics. The goals of this study were to detect CLA production in milk fermented with Lactobacillus casei strain AG and to measure the transcription levels of CLA synthesis-associated genes. Materials and Methods: CLA in fermented milk was detected by gas chromatography-mass spectrometry. The predicted homologous of the cla-hy, cla-dh and cla-dc genes were identified by polymerase chain reaction amplification. For CLA analysis, bacterial cultures were grown in media with or without the addition of 0.4 mg mL–1 linoleic acid. Results: Amplification products of the partial cla-hy, cla-dh and cla-dc homologous of the L. casei strain AG were obtained. The addition of linoleic acid did not change the transcription level of these genes compared to the control (p>0.05). Conclusion: Lactobacillus casei strain AG produced CLA in fermented milk but the genes involved in CLA synthesis were not induced by linoleic acid.